Skinny legs and all - Robbins, Tom, 1932- (Bantam Books, 1990)
When an Arab and a Jew open a restaurant across from the United Nations, New York City is turned on its ear, in a riotous, topical novel by the author of Half Asleep in Frog Pajamas.